Pathogenic organisms in the sputum of patients with chronic bronchitis - Wade, O. L. (1967)
Bacteriological examination of the early morning sputum from 54 patients with chronic bronchitis, half of whom received chemoprophylaxis with oxytetracycline, was made regularly for periods up to four and a half years. Nasal and perineal swabs were taken for periods up to three and a half years. There was no evidence that frequent or dangerous proliferation of drug-resistant organisms occurred in the sputum of patients on prolonged chemoprophylaxis with oxytetracycline nor that a serious increase of the carriage of drug-resistant Staphylococcus pyogenes occurred in the nares or on perineal skin. In patients receiving oxytetracycline there was a significant reduction in the frequency of identification of Streptococcus pneumoniae, but the organism was not eradicated: no significant change in the frequency of identification of Haemophilus influenzae was found. From year to year there was sometimes variation in the frequency of identification of Strep. pneumoniae and Strep. pyogenes in the sputum of these patients.